Antibiotic consumption among hospitalized neonates and children in Punjab province, Pakistan. Issue 6 (3rd June 2022) - Mustafa, Zia Ul; Salman, Muhammad; Yasir, Muhammad; Godman, Brian; Majeed, Hafiz Abdul; Kanwal, Mahpara; Iqbal, Maryam; Riaz, Muhammad Bilal; Hayat, Khezar; Hasan, Syed Shahzad
ABSTRACT: Background: Periodic surveillance of antibiotic consumption in the form of point prevalence studies is a quick and robust methodology to evaluate prescribing trends in hospitals. The current study was undertaken to document antibiotic consumption among neonates and children from hospitals in Pakistan. Methods: This large multicenter study using the World Health Organization standardized methodology and AWaRe (Access, Watch, and Reserve) classification examined antibiotic consumption for suspected bacterial infection among neonates and children admitted hospitals in Punjab, Pakistan. Results: A total of 708 beds of children wards of the 16 health facilities were examined. Almost all (97%) hospitalized children were prescribed antibiotics on the day of the assessment with 2.6 antibiotics per patient. The three most common indications were respiratory tract infections (31.58%), sepsis (26.52%), and prophylaxis for medical problems (10.30%). The three most frequently prescribed antibiotics were ceftriaxone (24.2%), amikacin (23.2%), and ampicillin (16.7%). Almost half of the antibiotics were prescribed from the 'Access' (49.5%) and 'Watch' (45.5%) categories under the AWaRe classification. However, no antimicrobial was prescribed from the 'Reserved' category. Conclusions: Our findings indicate that empirical antimicrobials use among hospitalized children is highly prevalent in Pakistan. The utilization of 'Watch' category of antimicrobials is frequent, stressing immediate action.